Langkah Sehat Tekanan Darah Terjaga Manfaat Jalan Kaki untuk Penderita Hipertensi Usia Produktif di Wilayah Kerja Puskesmas Pekkabata - Wahab, Masyitah; Nurfadhila, Nurfadhila (Yayasan Inspirasi El Burhani, 2025)
Introduction : Hypertension is a significant health issue, both in developed and developing countries, with a high prevalence in the productive age group. One effective non-pharmacological approach to managing hypertension is through physical activity, such as walking Objective : This community service activity aims to determine the benefits of walking in lowering blood pressure in individuals with hypertension in the productive age group (30-45 years) in the working area of Puskesmas Pekkabata. Method : The selected participants are individuals aged 30-45 years with hypertension, registered at Puskesmas Pekkabata. They were given an intervention program consisting of walking activities for 30 minutes daily, 3-5 times a week, for 4 weeks. Monitoring was conducted periodically to ensure participant compliance and measure changes in blood pressure before and after the intervention. Result : The results of this activity show a decrease in blood pressure in participants after regularly following the walking program. Based on these findings, it is recommended that walking be considered as a non-pharmacological treatment alternative to help manage hypertension and improve the quality of life of individuals with hypertension in the productive age group. Conclusion: This community service activity demonstrates that regular walking can provide significant benefits in lowering blood pressure in individuals with hypertension in the productive age group (30-45 years).